PENYULUHAN KESELAMATAN DAN KESEHATAN KERJA PADA OPERATOR PEMBUAT GULA JAWA DI DUSUN DUNGTILENG DESA SOMONGARI, KECAMATAN KALIGESING, KABUPATEN PURWOREJO, PROVINSI JAWA TENGAH - Mahrus Ali (UII, 2015)
Occupational Safety and Health of Operator of Sugar Makers in dusun Dungtileng have been overlookedyet. If it continues to be ignored, it can raise the risk of working.Therefore, it is necessary to counseling Health and Safety in the form of counselingworking environment (5S) and fix Occupational Posture (Musculoskeletal). With hopes,It can improve the quality of Occupational Safety and Health. Besides, it also couldincrease profit.